Kajian Musim Penangkapan Ikan Cakalang dengan Pole and Lineyang Didaratkan pada PT Radios Apirja, Sorong-Papua Barat - Mustasim Mustasim (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2016)
This study aimed to analyze the index skipjack fishing season which fishing base in PT Radios Apirja, Sorong-Papua Barat. Analysis of the data used is to use Presentation Methods average based on time series analysis that Determine the total catch per effort for each month for cascading data researched, created the series order CPUE per month for five years from 1 to 60, adding up the five CPUE each of the 12 months in five years, summing 60th CPUE, then a total of 60 CPUE divided by 12 to get an average per month in these five years. Total each CPUE respectively 12 months reduced by an average CPUE to get the index of catching season, and by using a chart or graph. The index value indicates that more than one fishing season, while the value of the index is less than 1 indicates no fishing season. The results showed that the business of catching skipjack by pole and line in the waters of Papua bird's head is done throughout the year, and catches fluctuate on a monthly basis, while the fishing season occurs from February to April and July to August.